Arthroscopic management of elbow stiffness - Joaquin Sanchez‐Sotelo (Journal of Experimental Orthopaedics, 2021)
Abstract The elbow is particularly prone to stiffness. Loss of elbow motion is very limiting, and can be the result of trauma, primary osteoarthritis, heterotopic ossification and other conditions. Several exposures have been described for open elbow contracture release. Although a few decades ago elbow arthroscopy was considered only for diagnosis and removal of loose bodies, contemporary arthroscopic techniques allow successful management of the majority of conditions leading to elbow stiffness. Careful patient evaluation, use of advanced imaging studies, and acquisition of appropriate surgical skills are essential for the successful arthroscopic management of the stiff elbow. This expert opinion reviews some fundamentals of elbow stiffness as well as principles for the evaluation and arthroscopic management of the stiff elbow.